2002
DOI: 10.1006/nimg.2002.1212
|View full text |Cite
|
Sign up to set email alerts
|

Linear Spatial Integration for Single-Trial Detection in Encephalography

Abstract: Conventional analysis of electroencephalography (EEG) and magnetoencephalography (MEG) often relies on averaging over multiple trials to extract statistically relevant differences between two or more experimental conditions. In this article we demonstrate single-trial detection by linearly integrating information over multiple spatially distributed sensors within a predefined time window. We report an average, single-trial discrimination performance of A z Ϸ 0.80 and fraction correct between 0.70 and 0.80, acr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
138
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(143 citation statements)
references
References 21 publications
4
138
0
1
Order By: Relevance
“…We compared the performance of the single-trial topographic analysis with two widely used single-trial classification techniques: logistic regression (Parra et al, 2002(Parra et al, , 2005Ratcliff et al, 2009) and SVM (Rieger et al, 2008;Taghizadeh-Sarabi et al, 2014). Despite similar levels of decoding performance across all subjects, the single-trial topographic analysis gave significant results at the single-subject level for more subjects than either of the two techniques.…”
Section: Comparison With Other Single-trial Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We compared the performance of the single-trial topographic analysis with two widely used single-trial classification techniques: logistic regression (Parra et al, 2002(Parra et al, , 2005Ratcliff et al, 2009) and SVM (Rieger et al, 2008;Taghizadeh-Sarabi et al, 2014). Despite similar levels of decoding performance across all subjects, the single-trial topographic analysis gave significant results at the single-subject level for more subjects than either of the two techniques.…”
Section: Comparison With Other Single-trial Methodsmentioning
confidence: 99%
“…The first one is logistic regression (Parra et al, 2002(Parra et al, , 2005, an algorithm which has been widely applied for studying perceptual decision-making (Philiastides and Sajda, 2006;Ratcliff et al, 2009) and in single-trial decoding in general (Brandmeyer et al, 2013;Farquhar and Hill, 2013). The second is Support Vector Machines (SVM), a powerful machine learning technique which has been used in various decoding applications (SVM; (Rieger et al, 2008;Salvaris and Sepulveda, 2009;Schulz et al, 2012;Taghizadeh-Sarabi et al, 2014)).…”
Section: Comparison With Other Single-trial Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify decision-related activity in the EEG signal, we used linear discrimination analysis as developed by Philiastides and colleagues (Parra et al, 2002;Philiastides and Sajda, 2006;Philiastides et al, 2006). Linear discriminant analysis performs logistic regression of binary data on multivariate EEG data to identify spatial weighting vectors (w) across electrodes that maximally discriminate between conditions of interest (e.g., a face or car stimulus).…”
Section: Experimental Designmentioning
confidence: 99%
“…It can occur when one hand is prepared and held in readiness for a delayed response (e.g., Leuthold, Sommer, & Ulrich, 1996;Osman et al, 1995; or when a hand response is prepared but then inhibited before its overt execution (e.g., De Jong et al, 1990;Miller & Hackley, 1992;Osman et al, 1992). Lateralized motor potentials can also occur during imagined movements of the hand (Beisteiner, Hollinger, Lindinger, Lang, & Berthoz, 1995;Osman, Müller, Syre, & Russ, 2005;Parra et al, 2002), as will be demonstrated here.The good temporal resolution of ERPs provides a number of avenues by which that portion of brain activity closely linked to a particular cognitive or behavioral event can be isolated from Regan, 1989). These ERPs are typically represented in the frequency domain, wherein power is plotted as a function of frequency.…”
mentioning
confidence: 65%